The Implementation of Restitution for Victims of Sexual Assault Against Children in Palangka Raya City - Sitholabi Sitholabi; Heriamariaty Heriamariaty; Rizki Setyobowo Sangalang; Louise Theresia (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2026)
The case of sexual intercourse against children is a serious crime that causes physical, psychological, and social impacts on the victim, so that the fulfillment of the right to restitution is a crucial element in legal protection for children, because it plays a role in the victim's recovery effort to return their condition as close as possible to the state before the crime occurred. This study aims to analyze the implementation of restitution for child victims of sexual intercourse in the jurisdiction of the Palangka Raya District Attorney's Office and examine the role and efforts of prosecutors in optimizing the implementation of restitution, including the factors that hinder it. The research method used is empirical legal research with a sociological juridical approach, which is carried out through a literature study of laws and court decisions, as well as interviews with relevant law enforcement officials, then analyzed qualitatively. The results of the study indicate that although restitution has been regulated normatively in various laws and regulations, its implementation has not been optimal due to the limited economic capacity of the perpetrator, the low understanding of victims and their families regarding the right to restitution, and the less than optimal coordination between prosecutors, law enforcement officials, and the Witness and Victim Protection Agency. This study concludes that optimizing restitution requires strengthening regulations, institutional readiness, and strong synergy between prosecutors, investigators, judges, and the LPSK so that protection can be realized effectively.